Sex-related Differences in Local and Whole-body Heat Loss Responses: Physical or Physiological? - Gagnon, Daniel (Université d'Ottawa / University of Ottawa, 2012)
The current thesis examined whether sex-differences in local and whole-body heat loss are evident after accounting for confounding differences in physical characteristics and rate of metabolic heat production. Three experimental studies were performed: the first examined whole-body heat loss in males and females matched for body mass and surface area during exercise at a fixed rate of metabolic heat production; the second examined local and whole-body heat loss responses between sexes during exercise at increasing requirements for heat loss; the third examined sex-differences in local sweating and cutaneous vasodilation to given doses of pharmacological agonists, as well as during passive heating. The first study demonstrates that females exhibit a lower whole-body sudomotor thermosensitivity (553 ± 77 vs. 795 ± 85 W•°C-1, p=0.05) during exercise performed at a fixed rate of metabolic heat production. The second study shows that whole-body sudomotor thermosensitivity is similar between sexes at a requirement for heat loss of 250 W•m-2 (496 ± 139 vs. 483 ± 185 W•m-2•°C-1, p=0.91) and 300 W•m-2 (283 ± 70 vs. 211 ± 66 W•m-2•°C-1, p=0.17), only becoming greater in males at a requirement for heat loss of 350 W•m-2 (197 ± 61 vs. 82 ± 27 W•m-2•°C-1, p=0.007). In the third study, a lower sweat rate to the highest concentration of acetylcholine (0.27 ± 0.08 vs. 0.48 ± 0.13 mg•min-1•cm-2, p=0.02) and methylcholine (0.41 ± 0.09 vs. 0.57 ± 0.11 mg•min-1•cm-2, p=0.04) employed was evidenced in females, with no differences in cholinergic sensitivity. Taken together, the results of the current thesis show that sex itself can modulate sudomotor activity, specifically the thermosensitivity of the response, during both exercise and passive heat stress. Furthermore, the results of the third study point towards a peripheral modulation of the sweat gland as a mechanism responsible for the lower sudomotor thermosensitivity in females.
Keywords: Temperature regulation; Sweating; Skin blood flow; Exercise; Heat; Thermoregulation